Pre-service teachers' voices of international teaching practicum in Indonesian elementary school - Setyaningsih, Ani; Diyanti, B. Yuniar; Nurhayati, Lusi (Diksi, 2023)
International teaching practicums help pre-service teachers (PSTs) advance professionally in teaching and gain multicultural competence. This study aims at describing an investigation of challenges and problems faced by the pre-service teachers during their international teaching program in an Indonesian elementary school and how to cope with them revealed by the PSTs' voices. This qualitative case study started with conducting a survey questionnaire covering various aspects of results, challenges, and problems regarding the aspects of pedagogical, content knowledge, technology, and cultural gaps faced by 7 international pre-service teachers (PSTs) from the Netherlands. The survey results were then further examined through in-depth interviews with the PSTs and thematic analysis was conducted to examine the data. The findings showed that there were three categories of problems faced by the PSTs: issues from the students, problems from the PSTs, and problems from the schools or stakeholders. The PSTs could adapt to the situation and find solutions to the problems. They tried to be "Indonesians," enjoyed every activity and difference, and communicated to the right person to solve the problems. The study also revealed that the PSTs hoped that the lecturers could have spent more time at school and given them more advice. They wished the university could improve the scheduling system and give them a chance to teach in more than one school to be able to experience different school cultures. This study recommends further investigation of how a good international teaching program should be developed and managed.Keywords: pre-service teachers, international teaching practicum, teaching English to young learners